Developing Speaking Activities in Students’ Textbook in Unit 2 Entitled Complimenting and Showing Care Based on Ctl for Senior High School Students - Oktaviana M.F.Q. Bobe; Rozario Mendonca Da Costa; Yustina Sako; Agustinus Seran; Adrianus Berek (Journal Innovation In Education, 2025)
This research was intended to develop speaking activities in students’ textbook for senior high school. This study aims to develop speaking materials based on Contextual Teaching and Learning (CTL). Based on the preliminary research, there was limited speaking activities in that textbook that can minimize the students to speak. The writers chose one topic to be developed entitled complimenting and showing care in the 2nd chapter. The reason of choosing that topic is that there are limited activities for speaking section. There are limited instructions used for students to express their idea orally. As we know that as a senior high school student, he or she has to be able to speak English orally. But if in the textbook does not provide enough instruction especially in speaking, it is useless. So the material should be developed. The writers is interested to develop that material in order to give the students opportunities to practice speaking orally based on their real life in learning English especially in speaking. Based on the result from previous findings, the writers expects that by giving some activities related to speaking, the students are able to express their idea orally. Because in that textbook limited of speaking activities that can minimize the students to speak, so the writers provided some instructional skill that can be useful for the students.